Elephant use and conflict leads to Tanzania’s first wildlife conservation corridor - Alfred Kikoti; Curtice Griffin; Lee Pamphil (Pachyderm)
Corridors linking protected areas are recommended for reducing the effects of human settlements that fragment African elephant (Loxodonta africana) home ranges and dispersal areas, and increase human-elephant conflicts. Community interviews and hilltop surveys were used in two Maasai villages in northern Tanzania in 2000 and 2001 to determine the extent of wildlife conflict, community attitudes towards elephants, and if elephants were using a vegetation corridor between the two villages to move between Tanzania and southern Kenya. Elephants were the most problematic species in the two villages adjacent to the corridor due to crop-raiding of primarily maize (Zea mays) and beans (Phaseolus vulgaris). Although villagers considered elephants a nuisance, they believed they attracted tourists, and generally did not believe elephant numbers should be reduced. Elephants used the corridor primarily in the wet and early dry seasons, and breeding herds were more numerous than bull herds. Based upon elephant conflict and use, and the communities’ need to maintain areas for cattle grazing and medicinal plant collection, the two Maasai communities established the first wildlife conservation corridor in Tanzania working in co-operation with government authorities and other stakeholders.